Occupational Therapy With Clothes Buttons To Improve Fine Motor Skills In Children With Moderate Disabilities At SLB N Slawi - Anisa Oktiawati; Erliana Dwi Nugraheni (International Journal of Midwifery and Health Sciences, 2024)
Mental retardation or blindness is a condition of incomplete mental development or general intellectual disorder below average and characterized by impaired developmental skills or more. Fine motor skills are factors that affect growth and development. In children, occupational therapy can improve fine motor skills. The prevalence data at SLB N Slawi shows that the proportion of children with disabilities amounts to 307 students, with the highest score, namely people with disabilities, as many as 259 students who are divided into two types, namely type C and type C1. The purpose of carrying out occupational therapy is to install clothing buttons to improve fine motor skills in children with moderate disabilities. This study was a descriptive research with a case study research design. The study subjects were patients with moderate impairment who experienced fine motor impairment. Data was obtained through interviews, observations, physical examinations, literature studies, and research instruments. This research was carried out in June 2024 at SLB N Slawi, and an ethical feasibility test has been carried out. The results of this study showed that fine motor skills in children with moderate disabilities in wearing buttons per day, which were measured and recorded on the observation sheet, improved. The improvement of fine motor skills is evidenced by the difference in scores in Child F at the beginning of the meeting got a score of 8 and was originally unable to do it, but did it with help, which increased to 15, namely being able to do it independently, and in patient Child N at the beginning of the meeting got 14 points and was originally able to do with the help increased to 16, namely being able to do independently. Patients with fine motor development disorders can be given occupational therapy by buttoning clothes once a day for 15-30 minutes.